THE EFFECT OF WORK ENVIRONMENT AND ORGANISATIONAL CULTURE ON WORK PRODUCTIVITY - Susilowati, Teti; Susiatin, Emy; Juhanes, Juhanes (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2023)
The purpose of this study was to analyse how the influence of work environment and organisational culture on employee productivity at PT Maju Bersama Gemilang, with a quantitative approach. The population in this study were all employees of the production department. The sampling technique used probability sampling as many as 76 employees as respondents in this study. The data processing method uses SPSS software. The data analysis tool used in this study is multiple linear regression. The results of this research indicate that the work environment has a significant effect on employee productivity. The results of the regression equation show that the work environment has a positive influence on employee productivity. The results of the calculation of organisational culture have a significant effect on employee work productivity. The results of the regression equation show that organisational culture has a positive influence on employee work productivity.